On the Dependence of the ice Formation in the Lake Ladoga on the Air Temperature - S. G. Karetnikov (Лëд и снег)
The purpose of the work was to establish regularities of the ice formation in the largest European Lake Ladoga depending on the air temperature. The average daily air temperatures obtained at the Sortavala weather station for thirty years were used for the analysis. The main task was to determine the sums of accumulated average daily air temperatures necessary for the appearance of primary ice phenomena in areas with different depths of the Lake. To solve this problem digitized remote sensing data of the spatial distribution of ice in the fixed cells with known average depth and data on average daily air temperatures were used. For thirty last winters, the dates of the first ice appearance in each of 180 cells were selected, which were related to the accumulated to this date sum of mean daily air temperatures after its steady transition through 0°С towards the negative values. The resulting scheme of the accumulated sums of air temperatures needed for the ice appearance indicates their regular growth with increasing depth. It is assumed that this dependence will make it possible to assess dynamics of ice formation on other lakes.